ANTIVIRAL ACTIVITY OF COPPER(II)CHLORIDE DIHYDRATE AGAINST DENGUE VIRUS TYPE-2 IN VERO CELL - Sucipto, Teguh Hari; Churrotin, Siti; Setyawati, Harsasi; Kotaki, Tomohiro; Martak, Fahimah; Soegijanto, Soegeng (Institute of Topical Disease Universitas Airlangga, 2017)
Infection of dengue virus (DENV) was number of globally significant emerging pathogen. Antiviral dengue therapies ar importantly needed to control emerging dengue. Dengue virus (DENV) is mosquito-borne arboviruses responsible for causing acute systemic diseases and grievous health conditions in humans. To date, there is no clinically approved dengue vaccine or antiviral for humans, even though there have been great efforts towards this end. Copper and copper compounds have more effective in inactivation viruses, likes an influenza virus and human immunodeficiency virus (HIV). Purpose in this project was investigated of Copper(II)chloride Dihydrate antiviral compound were further tested for inhibitory effect on the replication of DENV-2 in cell culture. DENV replication was measures by Enzyme linked Immunosorbent Assay (ELISA) with selectivity index value (SI) was determined as the ratio of cytotoxic concentration 50 (CC50) to inhibitory concentration 50 (IC50) for compound. The maximal inhibitory concentration (IC50) of Copper(II)chloride Dihydrate against dengue virus type-2 was 0.13 Î¼g/ml. The cytotoxic concentration (CC50) of compound against Vero cell was 5.03 Î¼g/ml. The SI values for Copper(II)chloride Dihydrate 38.69. Result of this study suggest that Copper(II)chloride Dihydrate demonstated significant anti-DENV-2 inhibitory activities and not toxic in the Vero cells. Copper mechanisms play an important role in the prevention of copper toxicity, exposure to excessive levels of copper can result in a number of adverse health effects, as a result increased reactive oxygen species and oxidative damage to lipid, DNA, and proteins have been observed in human cell culture models or clinical syndromes of severe copper deficiency and inhibition was attributed to released cupric ions which react with cysteine residues on the surface of the protease.